Performance prediction of prefabricated vertical drains beneath embankment on soft ground by finite element analysis - Thanath Gopalan, 1984-; Aminaton Marto, supervisor; Fakulti Kejuruteraan Awam (2010)
Thesis (Sarjana Kejuruteraan (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2010